2012
DOI: 10.1016/j.mambio.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of daylight regime on diurnal locomotor activity patterns of the European hare (Lepus europaeus) during summer

Abstract: a b s t r a c tKnowledge on diurnal locomotor activity pattern in wild nocturnal medium-sized mammals, such as the European hare (Lepus europaeus) is scarce. In this study, we tracked nine European hares during the vegetation period using GPS-transmitters. In particular, we focused on the question how the timing of sunset and sunrise influences the activity peaks in this species. The horal distances between two consecutive hare positions were used as a measure of locomotor activity. European hares showed two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Further, we compared diurnal movement activity for habitat generalists and specialists by testing the effects of time of day (numeric variable, in hours) in relation to the movement speeds within the same hour, in riparian thickets and agricultural land, separately. Since a non‐linear relationship between movement speed and time of day was expected with at least one activity peak, polynomials until the 7th order were used to model the data (Schai‐Braun, Rödel & Hackländer, ). Therefore, we applied “lmes” and the same modeling procedure described for habitat use.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we compared diurnal movement activity for habitat generalists and specialists by testing the effects of time of day (numeric variable, in hours) in relation to the movement speeds within the same hour, in riparian thickets and agricultural land, separately. Since a non‐linear relationship between movement speed and time of day was expected with at least one activity peak, polynomials until the 7th order were used to model the data (Schai‐Braun, Rödel & Hackländer, ). Therefore, we applied “lmes” and the same modeling procedure described for habitat use.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore used the Random Encounter Model (REM; Rowcliffe, Field, Turvey, & Carbone, ) to estimate the density D of mid‐sized and large herbivore prey as D=ytπVr(2+θ), where y is the number of independent photographic events, t is camera trap days (ctd), V is average speed of animal movement, and r and θ are the camera trap detection distance (in kilometer) and angle (in radian). Animal movement speeds were taken from the published literature with GPS fix frequencies of 15 min for red deer (Pépin, Adrados, Mann, & Janeau, ) and wild boar (Spitz & Janeau, ) and 1 hr for brown hare (Schai‐Braun, Rödel, & Hackländer, ). As there is no published data for movement speed of wild goat, we used movement speed of a wild goat collared in our subalpine study area with GPS fix frequency of 2 hr (Ambarlı, Hüseyin unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, European hares' home ranges include resting areas used during the day and feeding areas frequented at night (Averianov et al 2003), although during summer, the species' active period is not restricted to the dark phase (Holley 2001;Schai-Braun et al 2012). Studies analysing day and night habitat preferences separately confirmed that habitat preferences differ widely depending on the European hares' activity state (Tapper and Barnes 1986;Smith et al 2004;Cardarelli et al 2011;Bertolino et al 2011b).…”
Section: Introductionmentioning
confidence: 99%